Investigation of in vitro bioactivities of Zn-based hydroxyapatite samples doped with chitosan - Keser, Serhat; Efe, Harun (Springer, 2021)
In this study, the crystal structure, functional groups, morphological structure, elemental compositions, antimicrobial activity, and structural changes in the SBF of Zn-based HAp samples, synthesized by sol-gel method, doped with chitosan (CTS) at different amounts, were investigated. The crystal structure of the synthesized samples was determined by XRD technique, and the functional groups of the samples were determined by FTIR spectroscopy. The elemental compositions and morphologies of the HAp samples were investigated by SEM equipped with EDX spectroscopy. It was observed that the synthesized samples had antimicrobial activity. The effect of chitosan addition and immersing in SBF affected the crystallization percentages of the samples. No significant changes were observed in the morphology.
Keywords: Hydroxyapatite (HAp); SBF; Chitosan; Antimicrobial activity; Zn-doping; Crystal structure